Upaya Hukum Kasasi Penuntut Umum Atas Dasar Pembatalan Putusan Pengadilan Negeri Oleh Pengadilan Tinggi Dalam Kasus Tindak Pidana Narkotika - Afrizal Nur Fauzi; Kristiyadi, S,H., M.Hum - (Verstek, 2017)
This research aims is to find out the public prosecutor's appeal on the basis of the cancellation of Malang District Court Number 146/Pid.Sus/2014/PN.Mlg by the High Court of Surabaya with decision Number 364/Pid.Sus/2014/PT.SBY in criminal cases narcotics. In the case that I researched, the public prosecutor filed an appeal on the basis of Surabaya High Court had misapplied the law. The method used is a normative legal research. The approach used is the approach of legislation and conceptual approaches. Sources of legal materials used are primary and secondary legal materials. In this study, it has been known that the reason cassation prosecutor in narcotic cases on the basis of the cancellation of the decision of the District Court of Surabaya Malang by the High Court in accordance with the provisions of Article 253 the Code of Criminal Procedure Indonesia which according to Indonesia Supreme Court of Justice that High Court of Surabaya has missaplied the law in its decision about the mistakes made by the defendant is not without the right to sell, but as abusers of narcotics.        Keywords: Cassation, Cancellation Decision, Crime Narcotics